The attributes of commonly used cultural artefacts and their relations to diverse cultural practices - Perumal, Velu; Abd Rahman, Khairul Aidil Azlin; Raja Ahmad Effendi, Raja Ahmad Azmeer; Dolah, Mohd Shahrizal; S., Santhidran (Science Publishing Corporation, 2019)
Cultural artefacts are the identity of a culture and are important sources for creating novel design images. Malaysian design professionals face difficulties in creating designs that are novel and locally preferred. This is due to the plural and the autonomous cultural systems in Malaysia. As such this study aims to identify the commonly used cultural artefacts and the reason for their preferences. The nominal group technique (NGT) was used in this study to identify the commonly used cultural artefacts. NGT is a qualitative data collection technique based on discussions among various categories of stakeholders and multi-ethnic group members. The results from this study revealed the existence of 23 commonly used cultural artefacts and 18 attributes of these cultural, based on its appropriate function, convenient to use, simple structure, aesthetically pleasing and safe attributes. The findings in this study can help designers and design stakeholders to identify common cultural artefacts which can be their point of reference in creating multi-ethnically preferred design images.